2002
DOI: 10.1046/j.1365-2567.2002.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of the myeloid homeobox protein Hex is essential for normal T‐cell development

Abstract: SUMMARYThe haematopoietic homeobox gene Hex (also called Prh) is expressed in myeloid cells and B cells but not T cells. To investigate whether Hex levels might play a role in myeloid versus T-cell development, two types of transgenic mouse lines were constructed, each with ectopic expression of Hex in T cells (CD11a/Hex and Lck/Hex). Both these types of transgenic mouse had the same defects in T-cell maturation, indicating that proper T-cell development may be dependent not just on the up-regulation of lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 34 publications
(56 reference statements)
2
29
0
2
Order By: Relevance
“…24 HHEX may represent an important transcriptional target gene for this T-ALL subtype, as HHEX itself is sufficient to initiate self-renewal in thymocytes 73 and Hex can induce T cell-derived lymphomas when overexpressed in hematopoietic precursor cells in mice. 74 HHEX is highly expressed in normal hematopoietic stem cells and downregulation is necessary for normal T-cell development, 74,75 whereas most other hematopoietic lineages maintain HHEX expression. 76,25 So far, no genetic abnormalities of the HHEX gene itself have been found in human T-ALL, although fluorescence in situ hybridization analysis for possible translocations involving the HHEX locus has been extensively performed in patients 24 and T-ALL cell lines.…”
Section: Nkx2-5mentioning
confidence: 99%
“…24 HHEX may represent an important transcriptional target gene for this T-ALL subtype, as HHEX itself is sufficient to initiate self-renewal in thymocytes 73 and Hex can induce T cell-derived lymphomas when overexpressed in hematopoietic precursor cells in mice. 74 HHEX is highly expressed in normal hematopoietic stem cells and downregulation is necessary for normal T-cell development, 74,75 whereas most other hematopoietic lineages maintain HHEX expression. 76,25 So far, no genetic abnormalities of the HHEX gene itself have been found in human T-ALL, although fluorescence in situ hybridization analysis for possible translocations involving the HHEX locus has been extensively performed in patients 24 and T-ALL cell lines.…”
Section: Nkx2-5mentioning
confidence: 99%
“…13 Its promoter has been used previously to drive expression of gene to hematopoietic cells. 14,15 To investigate the role of EDAG in hematopoietic development, we engineered EDAG overexpression in hematopoietic cells of mice under the control of human CD11a promoter. Positive founder mice were identified by Southern blot analysis of tail DNA and RT-PCR of PB cells.…”
Section: Transgenic Edag Is Predominantly Expressed In Hematopoietic mentioning
confidence: 99%
“…The long latency of tumor incidence in Hex virus-transduced bone marrow recipients indicates that Hex-misexpressing cells must accumulate additional mutations to undergo neoplastic transformation. While MSCV-Hex:IRES:GFP-transduced marrow recipient mice develop T-cell lymphomas, transgenic mice expressing Hex in developing thymocytes from the CD11a and Lck promoters fail to develop such tumors (Mack et al, 2002), suggesting that the transformative events triggered by Hex misexpression occur prior to the stages at which the CD11a and Lck promoters are active. The oncogenic effects of Hex expression could be mediated by persistent low-level expression from Hex proviral insertions in multipotential cells in bone marrow or in committed precursors in bone marrow or thymus.…”
Section: Analysis Of Hex As a T-cell Oncogenementioning
confidence: 99%
“…Mice generated from chimeric blastocysts composed of HexÀ/À and RAGÀ/À ES cells are defective in normal B-cell development and function but have normal T-cell differentiation (Bogue et al, 2003). Recently, it has been demonstrated that transgene-driven expression of Hex in thymocytes disrupts normal T-cell development, resulting in fewer double-positive and more CD8 þ cells in the thymus and decreased numbers of T cells in the periphery (Mack et al, 2002).…”
Section: Introductionmentioning
confidence: 99%